2D α-MoO3-x truncated microplates and microdisks as electroactive materials for highly efficient asymmetric supercapacitors. (April 2022) - Salkar, Akshay V.; Naik, Amarja P.; Peña, Gerardo D. J. Guerrero; Bharath, G.; Haija, Mohammad Abu; Banat, Fawzi; Morajkar, Pranay P.
Highlights: 2D α-MoO3-x microstructures (truncated microplates (M1) and microdisks (M2)) are synthesized. Interaction of protonated urea with [Mo7 O24 ] 6-, and [Mo8 O26 ] 4- resulted in the formation of truncated microplates and microdisks. M1 exhibited remarkable energy and power densities of 41 W h kg -1 and 2108 W kg -1, respectively. The superior electrochemical performance is attributed to the presence of oxygen vacancies, lower solution resistance, and enhanced diffusion of H + ions. Abstract: Two-dimensional truncated microplates and microdisks of molybdenum oxide are synthesized, and their capabilities for superior performance in the charge storage devices are demonstrated. The chemistry of protonated urea with the heptamolybdate [Mo7 O24 ] 6− and octamolybdate [Mo8 O26 ] 4− ions is innovatively utilized to transform the MoO3-x nanoparticles into truncated microplates and microdisks, without the need of any expensive templates or hydro/solvothermal treatment. The 2D-MoO3-x truncated microplates and microdisks exhibit excellent supercapacitor performance with a high specific capacitance of 410 and 226 F g −1 at a remarkable current density of 20 A g −1 . The microstructures also exhibit substantial capacitance retention of > 90% and Coulombic efficiency > 98% for over 12000 continuous charge-discharge cycles, respectively. An asymmetric supercapacitor device of 2D MoO3-x microstructures has been assembled. The device exhibited remarkable energy and power densities of nearly 41 W h kg −1 and 2108 W kg −1 for MoO3-x truncated microplates, and 30 W h kg −1 and 2107 W kg −1 for MoO3-x truncated microdisks, respectively. Our method thus provides a route for facile fabrication of 2D MoO3-x microstructures which can function as excellent charge storage materials even at very high current densities while maintaining their electrochemical stabilities. Graphical abstract: Image, graphical abstract .